ANALISA PENGARUH SERVICE QUALITY TERHADAP BEHAVIORAL INTENTIONS DENGAN PERCEIVED VALUE DAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PENDIDIKAN TINGGI - Trixie Nova Bella Tandijaya (Jurnal Manajemen Pemasaran, 2018)
The importance of maintaining the quality of education of a country, making education in Indonesia also continues to make improvements both from the Elementary School level to the University level. At the University level alone, there is increasing competition between the State and Private Universities to produce more and more qualified graduates. So many universities are starting to think of strategies to win the competition. One of them by maintaining the Service Quality they provide. This study aims to determine the effect of Service Quality on Behavioral Intention or the tendency to behave, with perceived value and customer satisfaction as intervening variable high education students 2012-2016. The results of this study indicate that service quality has a positive and significant influence on perceived value and behavioral intentions, perceived value positively and significantly influence customer satisfaction and behavioral intentions, and customer satisfaction positively and significantly influence behavioral intentions. The results of this study also show that perceived value and customer satisfaction as intervening variables do not successfully mediate the relationship between service quality and behavioral intentions